Comparative Genomics of Aeromonas hydrophila Secretion Systems and Mutational Analysis of hcp1 and vgrG1 Genes From T6SS - Tekedar, Hasan C.; Abdelhamed, Hossam; Kumru, Salih; Blom, Jochen; Karsi, Attila; Lawrence, Mark L. (Frontiers in Microbiology, 2019)
Virulent Aeromonas hydrophila (vAh) causes severe motile Aeromonas septicemia (MAS) in warmwater fishes. In recent years, channel catfish farming in the U.S. and carp farming in China have been affected by vAh, and genome comparisons revealed that these vAh strains belong to the same clonal group. Bacterial secretion systems are often important virulence factors; in the current study, we investigated whether secretion systems contribute to the virulent phenotype of vAh. Thus, we conducted comparative secretion system analysis using 55 A. hydrophila genomes, including vAh strains from U.S. and China. Interestingly, tight adherence (TaD) system is consistently encoded in all the vAh strains. The majority of U.S. isolates do not possess a complete type VI secretion system (T6SS), but three core elements (tssD, tssH, tssI) are encoded. On the other hand, Chinese isolates have a complete T6SS operon. None of the vAh isolates have a type III secretion system (T3SS). Deletion of two genes encoding T6SS proteins (tssD and tssI) from vAh isolate ML09-119 reduced virulence 2.24 fold in catfish fingerlings compared to the parent strain ML09-119. These findings improve our understanding of A. hydrophila secretion systems and their role in virulence.